A New Narrative in Economic and Social Thinking - Muñoz Orozco, Javier (Sociedad y Economía, 2024)
The present study analyzes some of the ideas that govern people’s thinking in their incessant communication within the economic area of the social system, which form the basis of the narrative that drives them to act. The purpose was to identify elements of a new narrative for the present time. The ideas and proposals analyzed in the works of five authors in the field of social sciences served as a guide for this research. The principles of Grounded Theory (Glaser and Strauss, 1967/2006) and the qualitative method employed by Herzberg (1959) were observed, aiming to identify the metadiscourse—the essence of thought in the underlying content of the ideas expressed (Hyland, 1998). It was found that relationships of empathy and compassion, forming the basis of ethical interactions between individuals and groups, now direct the course of action in society.